A guide to the birds of Ceylon - Henry, G. M. (Kandy : K. V. G. De Silva and Sons, 1971)
1st published 1955.
First edition 1955.
Keywords: Birds; Sri Lanka; Birds - Sri Lanka - Pictorial works; Black Robin , -- Mynah , -- Sparrow , -- Woodpecker , -- Owl , -- Pigeon , -- Geese